Effects of postharvest application of 1‐methylcyclopropene on physiological disorders, crispness characteristic, and antioxidant capacity of "Concorde, " "Comice, " "Bosc, " and "Gem" pears. Issue 8 (26th April 2022) - Dong, Yu; Zhi, Huanhuan
Abstract: A complete understanding of European pears in response to 1‐MCP would deliver high‐quality pears with a crispy‐juicy texture to consumers. 1‐MCP reduced the incidences of decay, internal browning, and scald, suppressed ethylene production rate and respiration rate, and retained high flesh firmness and peel chlorophyll content in "Concorde, " "Comice, " "Bosc, " and "Gem" pears after 7 months of regular‐air storage plus a 5‐ or 7‐day ripening period. Additionally, high levels of total phenolics and flavonoids, DPPH, and ferric reducing antioxidant power were found in the 1‐MCP‐treated "Comice" and "Gem" pears, but not in "Concorde" or "Bosc". 1‐MCP effectively extended the storage life of "Concorde, " "Bosc, " and "Gem" pears to 5, 7, and 7 months, respectively, with high scores of crispness and juiciness. Conversely, a hard mouthfeel with fair juicy and flavor was found in the 1‐MCP‐treated "Comice" pears after 7 months of RA storage plus a 5‐day ripening at 20°C. Novelty impact statement: 1‐MCP retained the sensory attributes of flavor, juiciness, and crispness with low rates of disorders in "Concorde, " "Bosc, " and "Gem" pears over the 5, 7, and 7 months of regular‐air storage period, respectively. However, the hard mouthfeel with fair sensory attributes of juicy and flavor was obtained in 1‐MCP‐treated "Comice" pears. For consumers that prefer a ripened pear, pear industries could deliver the regular‐air‐stored "Concorde, " "Comice, " "Bosc, " and "Gem" pears during 1–3, 1–5, 0.5–3, and 1–5 months of storage, respectively.